Multi-therapeutic strategy targeting Akt-mTOR and FoxO1 pathway to counteract skeletal muscle atrophy consecutive to hypoxia - Bensaid, Samir; Fabre, Claudine; Yahya Rajaei, Amir; Claeyssen, Charlotte; Daussin, Frédéric N.; Cieniewski-Bernard, Caroline (American Journal of Physiology: Cell Physiology, 2025)
Our research demonstrates that combining electrical stimulation, BCAA supplementation, and oxygenation effectively counteracts hypoxia-induced muscle atrophy. Unlike isolated treatments, this multi-therapy approach significantly improves myotube morphology and regulates key protein homeostasis pathways, with mTOR activation protein and reduced myostatin expression. These findings highlight the enhanced therapeutic potential of combining physical activity, nutritional support, and oxygen therapy to prevent muscle atrophy in the detrimental reduction of oxygen supply. Chronic oxygen deprivation, whether due to high altitude or certain diseases such as cardiorespiratory pathologies, leads to muscle atrophy. To limit muscle loss, counteracting programs rely on only one therapeutic approach: return to sea-level altitude, physical activity, or nutritional supplementation. However, little effects are noticed on the muscle mass of subjects presenting severe hypoxemia. We hypothesized that the combination of several treatments (electrical stimulation and/or nutritional supplementation and/or oxygenation) would improve anabolic responses, thus counteracting efficiently hypoxia-induced muscle atrophy. In C2C12 myotubes submitted to hypoxia, we aim at testing several treatments based on the combination of electrical stimulation, amino acid supplementation, and/or an oxygenation period. In comparison with untreated muscle cells under hypoxia, all treatments had an anabolic impact on myotube morphology (myogenic fusion index, diameter, and density of myotubes), on proteosynthesis pathway [protein kinase B (Akt), mammalian target of rapamycin (mTOR), glycogen synthase kinase-3β, 4E-binding protein 1 (4E-BP1), and ribosomal protein S6 kinase (P70S6K)], on proteolysis pathway [Forkhead box protein O1 (FoxO1), myostatin, and ubiquitin-proteasome system], and on hypoxia marker (regulated in development DNA damage responses 1) protein level. Electrical stimulation alone resulted in hyperphosphorylation of Akt and FoxO1, whereas its combination with amino acid supplementation alleviated atrophy, exemplified by fusion index and myotube diameter increase up to 48 h post-application. Electrical stimulation followed by a period of oxygenation of hypoxic muscle cells strongly increased the activation status of 4E-BP1 and P70S6K. Finally, the simultaneous application of all treatments (electrical stimulation, amino acid supplementation, and oxygenation) was the only condition that resulted in activation of mTOR concomitantly with myostatin level decrease. These results support that the activation of the mTOR pathway through the combined application of electrical stimulation and branched-chain amino acids is strongly influenced by oxygen availability and that oxygen plays a critical role in optimizing the protein synthesis pathway in hypoxic skeletal muscle cells. NEW & NOTEWORTHY Our research demonstrates that combining electrical stimulation, BCAA supplementation, and oxygenation effectively counteracts hypoxia-induced muscle atrophy. Unlike isolated treatments, this multi-therapy approach significantly improves myotube morphology and regulates key protein homeostasis pathways, with mTOR activation protein and reduced myostatin expression. These findings highlight the enhanced therapeutic potential of combining physical activity, nutritional support, and oxygen therapy to prevent muscle atrophy in the detrimental reduction of oxygen supply.